Survey Study of Non-local College Students’ Attitudes Toward the Chongqing Dialect in Chongqing - Huang, Qi; Wu, Yuke (International Journal of Social Sciences and Public Administration, 2024)
This study aims to explore the linguistic attitudes of non-local college students in Chongqing towards the Chongqing dialect and to analyze how such attitudes affect their social integration in Chongqing. Through in-depth interviews with non-local college students from different provinces, the study found that although initially non-local college students had some difficulties in understanding and adapting to the Chongqing dialect, their acceptance of the dialect gradually increased with the increase in the time spent in Chongqing and they gradually began to use the dialect in their daily lives. This change in language attitude doesn’t not only reflects their gradual identification with the local culture, but also shows the key role of language in the process of cross-cultural adaptation. This study provides a new perspective for understanding the role of dialects in social integration and gives insights into how non-local students can better adapt to the local language environment.